Transannular ring closure of 10-membered cyclic diynes: model calculations - Haberhauer, Gebhard; Gleiter, Rolf (Journal of the American Chemical Society, 1999)
The transannular ring closure reaction of the 10-membered cyclic diynes cyclodeca-1,6-diyne (9a), 1,6-diazacyclodeca-3,8-diyne (9b), and 1,6-dioxacyclodeca-3,8-diyne (9c) to the corresponding bicyclo[4.4.0]deca-1,6-diene-2,7-diyl systems (11a−c) has been investigated using quantum mechanical methods. To optimize the geometries of the ground states, 9a−c, the transition states, 10a−c, and the intermediates, 11a−c, we employed the CASSCF(8,8)/6-31G* procedure. The inclusion of dynamic correlation (CASPT2[0] and CASPT2[g1]) approximations was necessary to reproduce the thermodynamic parameters obtained experimentally for 9a → 11a. Our calculations reveal that the activation energy for the ring closures 9 → 11 depends on the distance between the triple bonds. The alternative of the ring closure of 9a to bicyclo[5.3.0]deca-1,6-diene-2,6-diyl (13a) is predicted to occur at a higher activation energy (ca. 7 kcal/mol) than that for ring closure to 11a. A comparison with the Bergman cyclization reveals late transition states for 9a−c → 11a−c, in which the conjugation of the developing 4π system plays no role.